NCSC2 (ang. Nash Cascade-Submerged Cascade) − konceptualny model relacji opad-odpływ - Laskowski, Norbert; Kurnatowski, Jacek (Geology, Geophysics and Environment, 2024)
Conceptual hydrological models are an effective tool used to forecast runoff from catchments and assess changes in catchment dynamics. The article presents a modified concept of the Diskin parallel cascade model, with the replacement of one of the cascades with the submerged cascade model – the Nash cascade-submerged cascade model (NCSC2). Considering a watershed as a system where total runoff is determined by amounts of both surface and subsurface runoffs, the use of different model structures as surface and subsurface runoffs is reasonable. Adopting 13 different objective functions, the comparative analysis of NCSC2, Nash cascade, Diskin model, single linear reservoir and submerged reservoir cascade (SC2) models has been carried out in the catchment of six Polish rivers. The research has shown that the use of the submerged cascade as one of the Diskin model cascades positively affects the quality of the model.